A sound approach to choosing nonsteroidal anti-inflammatory drugs for osteoarthritis - E. V. Zonova; A. E. Karateev (Современная ревматология)
The current guidelines for prescribing analgesic therapy for osteoarthritis (OA) are based on the latest knowledge about the pathogenesis of this disease and the mechanism of action of analgesics. The leading principle of choosing analgesics is to assess the nature of pain and the patient's condition, adverse drug reactions. This is directly related to nonsteroidal anti-inflammatory drugs (NSAIDs) that are now the most important class of painkillers used in OA. Among the drugs of this class, meloxicam, a representative of the oxicam group, which relatively equally inhibits cyclooxygenase 1 and 2 and also affects the activity of microsomal prostaglandin E2 synthase 1, should be identified. This drug is characterized by a proven efficacy and a favorable safety profile. Nevertheless, the need for multifactorial evaluation of treatment-associated complications should be recognized as a priority when using any NSAIDs.